Problems of interchangeability of systemic interferons for treatment of multiple sclerosis - I. I. Snegireva; E. Yu. Pasternak; K. E. Zatolochina; M. A. Darmostukova; R. N. Alyautdin; V. A. Polivanov (Ministry of Health of the Russian Federation, Federal State Budgetary Institution «Scientific Centre for Expert Evaluation of Medicinal Products», 2018)
Problems of interchangeability of systemic interferons for treatment of multiple sclerosis are described. An analysis of 1,643 spontaneous reports existing in the Russian database for the period 2009 to 2015 was made in order to identify information on adverse reactions that occurred after replacement of systemically used interferons. Since 2010-2011 there have been reports on adverse reactions and lack of efficacy caused by the replacement of one systemic interferon for treatment of multiple sclerosis with another one with the same INN. Most of the reports indicated a «possible» degree of reliability of the cause-effect relationship. Most of the spontaneous reports of adverse reactions when replacing interferons beta-1a and beta-1b contained information about adult patients. More than half of the spontaneous reports of adverse reactions contained information on clinically signifiant events. When interferons beta-1a and beta-1b were replaced, there were mainly general disorders, reactions at the injection site, musculoskeletal disorders and neurologic disorders observed. The reference medication was well tolerated but replacing for a bioanalogous drug resulted in ineffectiveness or development of adverse reactions. The results of the study demonstrated that the data of spontaneous reports are important for making decision on the interchangeability of systemic interferons for the treatment of multiple sclerosis.